OPTIMALISASI RUTE PENGANGKUTAN SAMPAH DENGAN METODE ALGORITMA CLARKE AND WRIGHT SAVING DI KECAMATAN SINGAPARNA TASIKMALAYA - Mamik M. Fuadi; Wahyu Teri Aripin; Nurhalimah (Cipasung Techno Pesantren: Jurnal Ilmiah, 2023)
The increase in population in Tasikmalaya Regency, especially in Singaparna District was followed by an increase in the amount of waste produced. During the research activities, the Tasikmalaya Regency Environmental Service had a problem, namely the garbage transportation route was not optimal because the garbage transport route from the Temporary Disposal Site (TPS) to the Final Disposal Site (TPA) had several routes with vehicles carrying waste that exceeded the vehicle capacity. The method used to overcome this problem uses the Clarke and Wright Saving Algorithm. The results of calculations using the Clarke and Wright Saving Algorithm show that the total distance saved for all vehicles is 69.64 Km per week and the fuel costs saved are Rp. 44,830.74 per week. The results obtained show that routes created using the Clarke and Wright Saving Algorithm produce routes and fuel costs for transporting waste that are minimum than the existing routes.